The relationship between family health, stress, and self-efficacy on depression among university students: a large-scale national cross-sectional study - Zhihao Zhang; Wenyue Liu; Chen Zhang; Lezhong Sun (Frontiers in Public Health)
BackgroundDepression is a prevalent mental disorder globally, significantly impacting university students who face unique challenges such as academic and family pressures. This study investigates the prevalence of depressive symptoms among university students, examining the mediating role of stress in the relationship between family health and depressive symptoms, and the moderating role of self-efficacy in these relationships during COVID-19.MethodsA survey was conducted across various regions in China, collecting data from 1,193 university students. The instruments used included the Patient Health Questionnaire-9 to assess depressive symptoms, the Family Health Scale-Short Form to measure family health, the Subjective Life Stress Scale to evaluate stress levels, and the New General Self-Efficacy Scale to assess self-efficacy.ResultsThe results indicated a 26.8% prevalence of depressive symptoms among participants. Family health was found to negatively correlate with depressive symptoms, with stress mediating this relationship. Additionally, self-efficacy moderates both the direct and indirect effects of family health on depressive symptoms.ConclusionThis study underscores the need to develop comprehensive mental health strategies that consider the combined associations of family health, stress management, and self-efficacy with depressive symptoms among university students. It is particularly important to provide more effective support and interventions for the mental health of university students in the post-pandemic era.